Pattern of ABO and Rh Blood Groups among Voluntary Blood Donors at Nepal Red Cross Society Central Blood Transfusion Service Centre, Kalimati, Kathmandu - Singh, Smriti; Katwal, Barsika; Rijal, Tara Devi (Nepal Medical College Journal, 2024)
Blood is a circulatory fluid, responsible for the transport of hormones, nutrients, and enzymes all over the body. It consists of a protein-rich fluid known as plasma, in which are suspended cellular elements: white blood cells (WBC), red blood cells (RBC), and platelets. ABO blood grouping and cross-matching are commonly tested for transfusion of blood and its components, organ transplantation, genetic studies, forensic determinations, as well as for medico-legal issues such as paternity disputes. A descriptive cross-sectional study was conducted in Nepal Red Cross Society Central Blood Transfusion Service Centre, Kalimati, Kathmandu from January 1st 2023 to June 2023 done in 187 donors. Among 187 donors, the age of the donors ranged from 18 years to 55 years, with an average age of 35±0.58 years. The above figure showed that the majority (65.0%) fell into the age group of 26-40 years, followed by those aged 41-55 years, and finally, those aged 18-25 years, respectively. Among all voluntary donors, the majority (71.0%) were male, while 29% were female donors. Data analysis was done by using SPSS and MS-Excel. The result showed maximum number of voluntary donors to be of blood group O, followed by B, A and AB.